Pembentukan Indeks Pengukuran Kualitas Komunikasi: Strategi dalam Menangani Perilaku Menyimpang Remaja pada Siswa SMP - Sugito Sugito (UMSU, 2018)
This study aims to find out and produce an index measuring the quality of family communication as a strategy to deal with behavioral deviations among adolescents in Hikmatul Fadhillah Middle School students in Medan. This study uses a quantitative approach to the correlational method. The population is taken from adolescents aged 13-16 who will be chosen as research respondents. The research results identified based on openness still need to be improved. Most children sometimes avoid when parents are busy, this shows an empathy (empathy) attitude that needs to be instilled. People's support for the child is already running can be seen from the results of the questionnaire answers that are more like parents giving permission for things that excel. Positive feelings (positiveness) are very close to support so it is necessary for parents to participate in activities carried out by adolescents. Mutual respect and respect for both younger and older and telling each other is equality that occurs in family communication